2007
DOI: 10.1097/01.inf.0000247130.11902.64
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Single-Dose Ceftriaxone Versus Three Oral Antibiotic Regimens on Stool Colonization by Resistant Bacilli in Children

Abstract: A single intramuscular dose of ceftriaxone had a similar effect on the prevalence of antibiotic-resistant Gram-negative facultative bacilli in the stool of healthy children when compared with commonly used oral agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Previously, antibiotic‐related dysbiosis was believed to be transient (Welling et al, ; Cavallaro et al, ; Toltzis et al, ), but recent studies using molecular methods, most in mice or adults, have revealed that antibiotic‐associated changes in microbiota composition can be persistent. For example, microbiota differences persisted for up to 2 years in clindamycin‐exposed adults, compared with unexposed patients (Jernberg et al, ; Jernberg et al, ).…”
Section: Influences On Microbiotamentioning
confidence: 99%
“…Previously, antibiotic‐related dysbiosis was believed to be transient (Welling et al, ; Cavallaro et al, ; Toltzis et al, ), but recent studies using molecular methods, most in mice or adults, have revealed that antibiotic‐associated changes in microbiota composition can be persistent. For example, microbiota differences persisted for up to 2 years in clindamycin‐exposed adults, compared with unexposed patients (Jernberg et al, ; Jernberg et al, ).…”
Section: Influences On Microbiotamentioning
confidence: 99%
“…combination of organism and antibiotic). Studies involving S. pneumoniae resistant to either beta-lactams or macrolides, met this requirement and 13 studies [35,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] (n=11049 participants) were included in the analysis (Figure 1).…”
Section: Yield Of Search Strategymentioning
confidence: 99%
“…Since the bacteria causing UTI usually start life as bowel flora, this mechanism can directly increase likelihood of a child's UTI organism being resistant. 8 An individual predominantly colonised by a resistant organism is more likely to transmit a resistant rather than susceptible bacterium to an infectious contact (indirect effect). Finally an antibiotic treated individual, in whom their susceptible commensal flora has been eradicated, is more likely to acquire a new (resistant) bacterium (direct and indirect effects).…”
mentioning
confidence: 99%